2012
DOI: 10.1002/marc.201200313
|View full text |Cite
|
Sign up to set email alerts
|

Stress‐Induced Melting of Crystals in Natural Rubber: a New Way to Tailor the Transition Temperature of Shape Memory Polymers

Abstract: Lightly cross-linked natural rubber (NR, cis-1,4-polyisoprene) was found to be an exceptional cold programmable shape memory polymer (SMP) with strain storage of up to 1000%. These networks are stabilized by strain-induced crystals. Here, we explore the influence of mechanical stress applied perpendicular to the elongation direction of the network on the stability of these crystals. We found that the material recovers its original shape at a critical transverse stress. It could be shown that this is due to a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 27 publications
5
57
0
1
Order By: Relevance
“…As recently reported, the trigger temperature increases with rising programming temperature 23–25. We propose that this is possibly due to the growing crystal size.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…As recently reported, the trigger temperature increases with rising programming temperature 23–25. We propose that this is possibly due to the growing crystal size.…”
Section: Resultssupporting
confidence: 67%
“…Secondly, SMNR is the first example of a semi‐crystalline SMP with a significantly tunable trigger temperature 23. Thirdly, even after programming the trigger temperature can be adjusted by mechanically manipulating the stress transverse [stress‐induced melting (SIM)]24 and parallel [stress‐induced stabilizing (SIS)]25 to the elongation‐stabilizing direction. Finally, SMNRs have the capability to store extremely large strains of up to 1000% 23.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, recent study has shown that polymer crystals formed via strain-induced crystallization can be manipulated to precisely tune the melting temperature [312][313][314]. This may open up new ways to induce 2W-SME.…”
Section: Discussionmentioning
confidence: 96%
“…[ 19 ] Particularly interesting are polymer networks that not only respond to but also memorize an environmental signal. [ 22,23 ] Further, programmed SMNR strongly responds to liquids and gases by resuming its original shape. We hypothesize that this behavior might be found for those semi-crystalline networks where the change of the amorphous phase has a signifi cant impact on the stability of the crystals.…”
Section: Doi: 101002/adma201305698mentioning
confidence: 99%